Training and Installation of Solar Power Public Street Lighting for Karang Taruna at Bareng Village Klojen Malang Districs - Agus Setiawan; Sugeng Hadi Susilo; Elka Faizal; Ratna Monasari (Yayasan Payungi Smart Madani, 2022)
To improve security for residents in the area at ​​Bareng Village Klojen Malang Districts, one of the most important is lighting. The installation of public street lighting is still minimal, so it is far from meeting security and safety standards. In order to ensure the availability of safe and reliable street lighting, training on the assembly of solar-powered street lighting lamps (PJU) was carried out for members of the youth group RT10 RW 08 at Bareng Village Klojen Malang Districs. Prior to the assembly process for street lighting, a brief training was conducted on the assembly of solar-powered PJU light poles and their installation. Hence, they have skills that can be developed people. The result of assistance giving an increasing knowledge and skills of residents of RT10 RW 08 at ​​Bareng Village Klojen Malang Districts. This place in the fabrication and installation of solar-powered PJU lights. In addition, the installation of 3 Solar Powered PJU lights that are safe and reliable, and have an impact on increasing environmental security and residents' activities. Keywords: Solar Power, Public Street Lighting, Installation Solar Power